Lead for the victory: living and labor conditions for workers at the Chimkent lead plant (Journal of history, 2022)
Living conditions, including the production aspects of people’s livelihood are essential features of the level of society development. The studying of living conditions, labour of workers caused by both a catastrophic shortage of resources and insufficient thoughtfulness of the production process is a necessary condition for establishment an objective picture of the of Soviet society history. The given article scopes out and analyzes labor conditions of workers of defense enterprises, who made significant contribution to the improvement of the defense capability of the USSR in the context of social history approaches and the history of everyday life. The purpose and objectives of the presented article has been solved by introducing and analyzing a number of historical sources extracted by the authors from the archives of the Republic of Kazakhstan and the Russian Federation. Living conditions and labor of workers of defense enterprises are considered on the materials of the Chimkent lead plant, one of the main plants of the USSR for the production of lead. For its achievements the plant was named after M.I. Kalinin in 1935, further in 1939 the plant staff was awarded the highest award – Medal of Lenin. The importance of the plant especially increased during the war years, taking into account the shift of the industrial center of the USSR to the East. Finally, the article presents the authors’ conclusions about the deterioration of the working conditions of employees and increasing of the cases of injuries and diseases during the War.